The role of parent-teacher involvement in child adjustment and behaviour in child-care centres - Pirchio, Sabine; Volpe, Elena; Taeschner, Traute (International Journal about Parents in Education, 2023)
Many studies have shown that parent-teacher collaboration results in better school performances and social skills (Arnold, Zeljo, Doctoroff, & Ortiz, 2008; Comer, 1984; 1988; Izzo & Weissberg, 1999; Kohn & Zellman, 1994; Marcon, 1999; McNeal, 1999; Taylor & Machida, 1994). The role of the relationship between parents and educators in the child’s development and wellbeing is relatively unexplored in infancy and early childhood. This work investigates the relationship between the child’s behaviour, the parent-teacher relationship and the parents’ satisfaction with aspects of care and provision in day-care centres. The study involved 100 families of children (48 boys; average age 27.7 months) attending 5 day-care centres, and 29 day-care educators. A questionnaire was given to the parents to assess their child’s temperament, attitudes toward the day-care activities and services and parent-teacher involvement. Day-care educators filled in a questionnaire on job satisfaction, children’s problematic behaviour and parent-teacher involvement. Results show that parents’ satisfaction with material features is associated with their satisfaction with educational features of the day-care. Parent-teacher involvement assessed by parents is negatively associated with parents’ age, education and satisfaction with the day-care services, and is positively correlated with the child’s social orientation, emotional development and motor activity.